The Impact of Nature Exposure on Mental Health and Well-Being - Rahaju Ningtyas; Nurhikmah Paddiyatu; Benny Novico Zani; Herawati; Sandy Novryanto Sakati (West Science Interdisciplinary Studies, 2023)
This research investigated the impact of nature exposure on mental health and wellbeing in West Bandung Regency, Indonesia, a region characterized by diverse natural landscapes. A mixed-method approach combining quantitative surveys and qualitative interviews was employed to gather data from residents of various communities in the region. The quantitative findings indicated that more frequent nature exposure was associated with lower levels of stress, anxiety, and depression. The qualitative insights revealed that nature exposure provided a sense of relaxation, tranquility, and rejuvenation, enhancing emotional well-being. The study underscores the restorative effects of nature and the importance of integrating green spaces into urban planning to promote mental health in rapidly developing regions like West Bandung Regency.